2015
DOI: 10.1093/jxb/erv102
|View full text |Cite
|
Sign up to set email alerts
|

A tomato chloroplast-targeted DnaJ protein protects Rubisco activity under heat stress

Abstract: Photosynthesis is one of the biological processes most sensitive to heat stress in plants. Carbon assimilation, which depends on ribulose-1,5-bisphosphate carboxylase/oxygenase (Rubisco), is one of the major sites sensitive to heat stress in photosynthesis. In this study, the roles of a tomato (Solanum lycopersicum) chloroplast-targeted DnaJ protein (SlCDJ2) in resisting heat using sense and antisense transgenic tomatoes were examined. SlCDJ2 was found to be uniformly distributed in the thylakoids and stroma o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
50
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(60 citation statements)
references
References 47 publications
4
50
0
1
Order By: Relevance
“…During the 7-day heat wave period, leaf senescence and reduction in chlorophyll content were observed in well watered plants, which is supported by other studies (Marchand et al 2006; Wang et al 2015). For example, Wang et al (2015) found that tomato grown under 42 °C for 24 h had significantly lower chlorophyll content than that grown under 25 °C. In the present study, the very high leaf temperature ( i.e .…”
Section: Discussionsupporting
confidence: 90%
“…During the 7-day heat wave period, leaf senescence and reduction in chlorophyll content were observed in well watered plants, which is supported by other studies (Marchand et al 2006; Wang et al 2015). For example, Wang et al (2015) found that tomato grown under 42 °C for 24 h had significantly lower chlorophyll content than that grown under 25 °C. In the present study, the very high leaf temperature ( i.e .…”
Section: Discussionsupporting
confidence: 90%
“…Previous researchers had reported that the DnaJ protein was involved in plant response to heat and drought stresses (Xia et al, 2014; Wang et al, 2015). To further comprehend the putative roles of CaDnaJ genes in pepper response to HS, expressions patterns of CaDnaJ genes under HS treatment conditions were analyzed by qRT-PCR.…”
Section: Discussionmentioning
confidence: 99%
“…Immuno-blotting was conducted as described by Wang et al (2015). The anti-FLAG antibody was purchased from Sigma-Aldrich (A8592).…”
Section: Subcellular Localization Of Slwhy1mentioning
confidence: 99%